DETERMINANTS OF EMPLOYEES’ ATTITUDE TOWARD UNION MEMBERSHIP (Study Case In A Logistics Company In Indonesia) - Ranggapati Siswara Dewantoro; Riani Rachmawati Sobri; Muhammad Irfan Syaebani (Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
This research examines the determinants of employees’ attitude toward union membership. These factors are represented by job-related predictor such as; employees’ job dissatisfaction, job stress, and consultative managerial style. Apart from these job-related predictor variables, the cultural orientation played a role in this research such as; individualism and collectivism both horizontal and vertical. After performing resgression testing, the result shows that almost all variables are affecting employees’s attitude toward union membership except horizontal collectivism variable.